2020
DOI: 10.1039/d0ra03478a
|View full text |Cite
|
Sign up to set email alerts
|

Advances in PEG-based ABC terpolymers and their applications

Abstract: Design, synthesis, and applications of PEG-based ABC terpolymers were highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 110 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Considering the application of miktoarm star polymer in drug delivery, poly(caprolactone) (PCL) and poly(ethylene glycol) (PEG) is selected as a hydrophobic and hydrophilic arm owing to good biocompatibility. 46 Referring to the coarse-grained method by Lin et al , 11 PCL and PEG are divided into beads A and C, respectively. PDEA is selected as pH-responsive arm and divided into two kinds of beads, B in the main chain and D in the side chain.…”
Section: Methods and Model Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the application of miktoarm star polymer in drug delivery, poly(caprolactone) (PCL) and poly(ethylene glycol) (PEG) is selected as a hydrophobic and hydrophilic arm owing to good biocompatibility. 46 Referring to the coarse-grained method by Lin et al , 11 PCL and PEG are divided into beads A and C, respectively. PDEA is selected as pH-responsive arm and divided into two kinds of beads, B in the main chain and D in the side chain.…”
Section: Methods and Model Detailsmentioning
confidence: 99%
“…Considering the application of miktoarm star polymer in drug delivery, poly(caprolactone) (PCL) and poly(ethylene glycol) (PEG) is selected as a hydrophobic and hydrophilic arm owing to good biocompatibility. 46 Referring to the coarsegrained method by Lin et al, 11 The choice of the interaction parameters a ij in Table 1 in this work is made following the calculation of a previous publication by Lin et al, 13 who carried out molecular dynamics simulation to obtain Flory-Huggins parameters. Using these parameters and combining with experiments, their DPD simulations have been applied to investigate the structure-property relationship of micelles formed by A 2 (BC) 2 miktoarm star polymers.…”
Section: Model and Parametersmentioning
confidence: 99%
“…Due to its simplicity in formulation, high hydrophilicity, and biocompatibility, hydrophilic polyethylene glycol (PEG) was frequently employed in earlier studies in combination with lipophilic drugs in order to circumvent the solubility and bioavailability issues associated with free pharmaceuticals (95). In addition to self-assembling into various nano formulations, such as polymeric micelles, PEG-based prodrugs also co-deliver the water-insoluble chemotherapeutics included in their hydrophobic core, which results in synergistic anti-cancer efficacy (96). Recently, a study demonstrated that platinum Pt (IV) prodrugs based on cisplatin and chemosensitizer adjudin (ADD), which had the capacity to self-assemble into nanosheets, improved the sensitivity of cisplatin to triple-negative breast cancer.…”
Section: Self-assembly Prodrugmentioning
confidence: 99%